2007
DOI: 10.1007/s11250-007-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Sweet potato and Green panic as sole fodder for stall-fed lactating White Fulani cows and growing calves

Abstract: Three sweet potato varieties (TIS-87/ 0087; TIS-8164; TIS-2532.OP.1.13) and Green panic (Panicum maximum) were evaluated for forage quality in a completely randomized design (CRD) using 12 sole-fed lactating White Fulani cows for 21 days, and 12 growing White Fulani and White Fulani x Brown Swiss calves for 77 days. Dry matter intake of cows ranged (p<0.05) between 131 g/Wkg(0.734) in TIS-87/0087 and 152 g/Wkg(0.734) in TIS-8164. Daily milk yields increased (p<0.05) in TIS-87/0087 (2%) and TIS-8164 (5%), but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Sampath et al (1989) working with adult crossbred bullocks fed 1.5-kg concentrate plus 10-kg green fodder plus ad libitum rice paddy, reported 50.64 ± 0.29% rumen DM degradation for Guinea grass after 48-h incubation. A recent study with the same varieties on Bunaji cows and calves indicated that sole feeding sweet potato foliage would be beneficial to ruminants without any observable incidence of toxicity (Etela et al, 2008). Or under most practical situations it could be utilized as supplement for improving poor quality dry-season diets based on grasses such as Guinea grass.…”
Section: Discussionmentioning
confidence: 99%
“…Sampath et al (1989) working with adult crossbred bullocks fed 1.5-kg concentrate plus 10-kg green fodder plus ad libitum rice paddy, reported 50.64 ± 0.29% rumen DM degradation for Guinea grass after 48-h incubation. A recent study with the same varieties on Bunaji cows and calves indicated that sole feeding sweet potato foliage would be beneficial to ruminants without any observable incidence of toxicity (Etela et al, 2008). Or under most practical situations it could be utilized as supplement for improving poor quality dry-season diets based on grasses such as Guinea grass.…”
Section: Discussionmentioning
confidence: 99%
“…In small farm systems, supplementing the diet with SPV or CF as a protein source for ruminants that were being fed poor quality roughages, improved animal productivity and economic efficiency (Wanapat 2009). Although supplementing basal tropical forage diets with SPV improved apparent nutrient digestion (Etela et al 2008a(Etela et al , 2009, feeding SPV at more than 30% of DM caused a reduction of protein and NDF digestibility (Aregheore 2004;Megersa et al 2013). Although supplementing basal tropical forage diets with SPV improved apparent nutrient digestion (Etela et al 2008a(Etela et al , 2009, feeding SPV at more than 30% of DM caused a reduction of protein and NDF digestibility (Aregheore 2004;Megersa et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although SPV has similar neutral detergent fiber (NDF) content as AH, its crude protein (CP) content, ruminal effective degradability, and degradation rate of dry matter (DM) are lower than those of AH (Kariuki et al 1998;National Agriculture and Food Research Organization (NARO) 2009). Although supplementing basal tropical forage diets with SPV improved apparent nutrient digestion (Etela et al 2008a(Etela et al , 2009, feeding SPV at more than 30% of DM caused a reduction of protein and NDF digestibility (Aregheore 2004;Megersa et al 2013). Thus, the use of SPV as a major roughage source may have negative effects on ruminant production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crop is a source of dietary ber, complex carbohydrates, proteins, vitamins A, C and B, iron, calcium as well as making of industrial starch (Korada et al 2010). The immature leaves are consumed as vegetable (Masumba et al 2007), and also for animal feed (Etela et al 2008). Furthermore, the crop is easy to produce at rural level with minimum input, due to its tolerance to a wide range of edaphic and climatic condition, low demands on soil nutrients, low requirements for external inputs such as fertilizers, exibility in planting and harvesting periods (Lebot 2009).…”
Section: Introductionmentioning
confidence: 99%